2012
DOI: 10.1063/1.4771983
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of antiferroelectric state in NaNbO3 at high pressure from in situ neutron diffraction

Abstract: We report direct experimental evidence of antiferroelectric to paraelectric phase transition under pressure in NaNbO 3 using neutron diffraction at room temperature. The paraelectric phase is found to stabilize above 8 GPa and its crystal structure has been determined in orthorhombic symmetry with space group Pbnm.The variation of the structural parameters of the both orthorhombic phases as a function of pressure was determined. We have not found evidence for structural phase transition around 2 GPa as previou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 33 publications
0
14
1
Order By: Relevance
“…On lowering the temperature, it undergoes transition to a series of antiferrodistortive phases in this order: tetragonal (T2) P4/mbm, orthorhombic (T1) Cmcm, orthorhombic (S) Pbnm, orthorhombic (R) Pbnm, orthorhombic (P) Pbcm phases, and a rhombohedral R3c phase . Pressure‐induced phase transition from room temperature antiferroelectric orthorhombic ( P bcm ) phase to paraelectric orthorhombic ( P bnm ) phase is also reported in literature . These structural phase transitions involve phonon mode instabilities linked with zone centre and zone boundary phonon modes with respect to the cubic phase .…”
Section: Introductionmentioning
confidence: 99%
“…On lowering the temperature, it undergoes transition to a series of antiferrodistortive phases in this order: tetragonal (T2) P4/mbm, orthorhombic (T1) Cmcm, orthorhombic (S) Pbnm, orthorhombic (R) Pbnm, orthorhombic (P) Pbcm phases, and a rhombohedral R3c phase . Pressure‐induced phase transition from room temperature antiferroelectric orthorhombic ( P bcm ) phase to paraelectric orthorhombic ( P bnm ) phase is also reported in literature . These structural phase transitions involve phonon mode instabilities linked with zone centre and zone boundary phonon modes with respect to the cubic phase .…”
Section: Introductionmentioning
confidence: 99%
“…In the present study the Na-deficiency is considered to play an important role in forming Table 1 Summary of the Rietveld refinement results for the TOF neutron data for the candidate models. Both the powder sample obtained by pulverizing the sintered pellet at 1573 K (upper part) (1) and the pellet sample (lower part) (2) were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Pulverized pellet (1) Pcmb ( a R-factors with weighted profile pattern (R wp ), pattern (R p ), Bragg factor (R b ), structure factor (R f ), and goodness-of-fit (χ2¼ R wp /R e ) 2 (R e : expected-R). the two phases.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…It is found that the antiferroelectric phase transforms to the ferroelectric phase (space group: Pmc2 1 ) on small substation of Na + ion by Li + . These structural phase transitions involve cationic displacement and tilting of the oxygen octahedra and have been characterized by various techniques such as X‐ray and neutron diffraction and Raman spectroscopy …”
Section: Introductionmentioning
confidence: 99%